Europium-labelled nanopolystyrene as model nanoplastics for environmental fate investigations: Synthesis and optimisation - Rega Permana; Swati Sharma; Christopher Stark; David Price; Christian Pfrang; Eugenia Valsami-Jones (Polymer Testing, 2025)
Nanoplastics (NPLs) have emerged as pervasive environmental contaminants, reaching remote regions and even crossing biological barriers such as the human blood-brain barrier. Their biomolecule-like composition, primarily composed of carbon and hydrogen, complicates detection using conventional analytical methods. To overcome this challenge, a tracer-doped plastic matrix was developed to enable rapid and precise detection, tracking, and analysis of NPLs. In this study, europium (Eu), a rare-earth metal, was used to label polystyrene-based NPLs, chosen for their abundance in environmental samples. The NPLs were synthesised through a two-step dispersion polymerisation process involving styrene (monomer), potassium persulfate (initiator), sodium dodecyl sulfate (surfactant), and Eu (dopant). Response Surface Methodology with Central Composite Design (RSM-CCD) was employed to optimise the synthesis parameters, and ANOVA confirmed the model's significance and robustness. The suitability of the labelling technique was confirmed by measuring the Eu-doped NPLs using single-particle inductively coupled plasma mass spectrometry (SP-ICP-MS). The results demonstrated a strong linear relationship between the concentration of Eu dopant, the total mass of the Eu-doped NPLs, and the number of individual Eu-doped NPL particles. Under optimised conditions the NPLs achieved a hydrodynamic size of 121.47 ± 0.89 nm and a dopant concentration of 0.12 wt%. Leaching tests conducted over seven days in deionised water (DIW) and artificial seawater (ASW) showed less than 0.5 % dopant loss, indicating robust encapsulation of Eu within the polymer matrix. This labelling approach provides a reliable method for the quantitative analysis of NPLs, enabling more accurate assessments of their behaviour and toxicity in various environmental contexts.